As contribuições de Antonio Gramsci para a educação e formação humana da frente única - Sousa, Nágela da Silva de (2013)
The dissertation aims to investigate the categories present in the work of the Italian revolutionary Antonio Gramsci, pinpointing his proposal of a united front and its educational construction in the perspective of the revolution; revisiting the contributions of theorists and scholars in line with the thought of Gramsci, as it relates to worker-peasant Alliance in view of proletarian revolution, Del Roio (2005) e Nosella (1992), for example. Based upon historical dialectic materialism, the paper followed a set of theoretical-bibliographic procedures of a classist character, adopting as its major reference, the production of Antonio Gramsci, a true militant theorist of proletarian cause, specifically his pre-prison work; and political writings, in general. In this way, we seek to historically retrieve the genesis and evolution of Antonio Gramsci’s thought, consolidated in his short life trajectory, highlighting elements linked to his family origin, as his theoretical-practical militancy, marked by a deep immersion in the political and social class struggles in Italy, in particular, his involvement with the problematics of the factories councils and the school of labor. Generally speaking, in the analysis of the context of the Southern Issue in Italy, expressed in political-geographical division, we feature the revolutionary conceptions of Gramsci, in function of subalternity. Attempting to understand the labour movement, we situate the French experience in the 19th century from the reference point of the 18 Brumaire of Louis Bonaparte, of Karl Marx, reporting the peasants struggles. Further on, from the Marxian ontology frame of reference, and understanding education as a complex founded by work, we focus upon the united front and its complexities, tracing the role of education and/or human formation for the constitution of a worker-peasant Alliance in the context of the Italian situation of the early 20th century, showing the character at the same time particular and universal of Gramscian contributions.